Modeling and simulation of CNTFET small signal model - Farhana, Soheli; Alam, A. H. M. Zahirul (2014)
The progress of Carbon Nanotube Field Effect Transistor (CNTFET) devices has facilitated the trimness of mobile phones, computers and all other electronic devices. CNTFET devices contribute to model these electronics instruments that requires to design the devices. This research dig out the CNTFET device's small signal model. Scattering parameters (S-parameters) is extracted from the CNTFET model to construct equivalent small model circuit. Current sources, capacitors and resistors are involved to evaluate this equivalent circuit. S-parameters and small signal models are elaborated to analyze using a technique to form the small signal equivalent circuit model. In this design modeling process, at first intrinsic device's Y-parameters are determined. After that series of impedances are calculated. At last, Y-parameters model are transformed to add paracitic capacitances. The analysis result shows the acquiring high frequency performances are obtained from this equivalent circuit.